2014
DOI: 10.1016/j.jhsa.2014.06.094
|View full text |Cite
|
Sign up to set email alerts
|

PXL01 in Sodium Hyaluronate for Improvement of Hand Recovery After Flexor Tendon Repair Surgery: Randomized Controlled Trial

Abstract: Background: Postoperative adhesions constitute a substantial clinical problem in hand surgery. Fexor tendon injury and repair result in adhesion formation around the tendon, which restricts the gliding function of the tendon, leading to decreased digit mobility and impaired hand recovery. This study evaluated the efficacy and safety of the peptide PXL01 in preventing adhesions, and correspondingly improving hand function, in flexor tendon repair surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Four high-quality RCTs were found (Tab. X) [143][144][145][146] . HA products with higher molecular weight and longer half-life favor a greater permanence of HA into intrasynovial peritendinous space compared to native HA and low molecular weight formulations, ensuring greater clinical efficacy.…”
Section: Hyaluronic Acid In Tendon and Bursamentioning
confidence: 99%
“…Four high-quality RCTs were found (Tab. X) [143][144][145][146] . HA products with higher molecular weight and longer half-life favor a greater permanence of HA into intrasynovial peritendinous space compared to native HA and low molecular weight formulations, ensuring greater clinical efficacy.…”
Section: Hyaluronic Acid In Tendon and Bursamentioning
confidence: 99%
“…Closest to clinical translation include pharmacological agents that inhibit adhesions. Lactoferrin-derived peptide PXL01, formulated in sodium hyaluronate, significantly improves mobility without any negative effect on healing strength demonstrated in animal models (Hakansson et al, 2012) and early clinical trials (Wiig et al, 2014). Hyaluronic acid in a variety of forms, including carbodiimide-derivatized hyaluronic acid combined with Lubricin (cd-HA-Lubricin), can modulate tendon surface quality, which eliminates graft adhesions and improves digit function in a canine model, whereas clinical efficacy has also been shown in randomized controlled trials.…”
Section: Basic Science Strategies To Solving the Problemmentioning
confidence: 99%
“…8 A few AMPs have been carrying clinical trials, human cathelicidin member LL-37 to promote the healing of venous leg ulcers 9 and PXL01, derived from human lactoferricin, to prevent postsurgical adhesion formation (NCT01022242) were conducted. 10,11 We first reported that the cathelicidin family of AMPs exists in reptile species of Naja atra, Bungarus fasciatus, and Ophiophagus hannah snake species. 12 We focused on cathelicidin from king cobra (OH30) and revealed that this peptide has strong antibacterial activity against various bacteria in the presence of 1% NaCl.…”
Section: Introductionmentioning
confidence: 99%